Carbon nanotube-modified sodium dodecyl sulfate-polyacrylamide gel electrophoresis for molecular weight determination of proteins - Parthasarathy, Meera; Debgupta, Joyashish; Kakade, Bhalchandra A.; Ansary, Abu Ayoobul; Khan, Mohammad Islam; Pillai, Vijayamohanan K. (Analytical Biochemistry, 2011)
The effect of incorporating carbon nanotubes (CNTs) in the gel matrix on the electrophoretic mobility of proteins based on their molecular weight differences was investigated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). More specifically, a reduction in standard deviation in the molecular weight calibration plots by 55% in the case of multiwalled carbon nanotubes (MWCNTs) and by 34% in the case of single-walled carbon nanotubes (SWCNTs) compared with that of pristine polyacrylamide gels was achieved after incorporating an insignificant amount of functionalized CNTs into the gel matrix. A mechanism based on a more uniform pore size distribution in CNT modified polyacrylamide gel matrix is proposed. Furthermore, the impact of SWCNTs and MWCNTs on the mobility of proteins in different molecular weight regimes at a given acrylamide concentration offers a tunable gel matrix in terms of the selection of molecular weight ranges of proteins. The robustness and excellent reproducibility of the CNT-PAGE protocol are expected to have a significant impact on the molecular weight determination of newly isolated proteins. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Carbon nanotubes; Gel electrophoresis; Molecular weight determination; Polyacrylamide; Protein separation

Competitive wetting of acetonitrile and dichloromethane in comparison to that of water on functionalized carbon nanotube surfaces - Debgupta, Joyashish; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Physical Chemistry Chemical Physics, 2011)
Differential wetting of pristine and ozonized carbon nanotubes has been studied using solvents like acetonitrile and dichloromethane in comparison to the well-known wetting behavior of water. Based on their unique structural and physical properties, functionalized CNT substrates have been used due to the fact that independent variation in molecular as well as electronic properties could be controlled by understanding the wetting of these liquids on carbon nanotubes (CNTs), both pristine as well as ozone treated. The sensitivity of the wetting behavior with respect to molecular interactions has been investigated using contact angle measurements while Raman and XPS studies unravel the differential wetting behavior. Charge-transfer between adsorbed molecules and CNTs has been identified to play a crucial role in determining the interfacial energies of these two liquids, especially in the case of acetonitrile. Ozone treatment has been observed to affect the surface properties of pristine CNTs along with a concomitant change in the wetting dynamics.

Charge transport in functionalized multi-wall carbon nanotube-Nafion composite - Sangeeth, C. S. Suchand; Kannan, Ramaiyan; Pillai, Vijayamohanan K.; Menon, Reghu (Journal of Applied Physics, 2012)
The charge transport in sulfonated multi-wall carbon nanotube (sMWNT)-Nafion composite is reported. The scanning electron microscope images of the composite, at 1 and 10 wt % of sMWNT, show that the nanotubes are well dispersed in polymer matrix, with conductivity values of 0.005 and 3.2 S/cm, respectively; and the percolation threshold is nearly 0.42 wt. %. The exponent (similar to 0.25) of the temperature dependence of conductivity in both samples indicates Mott's variable range hopping (VRH) transport. The conductance in 1 wt. % sample increases by three orders of magnitude at high electric-fields, consistent with VRH model. The negative magnetoresistance in 10 wt. % sample is attributed to the forward interference scattering mechanism in VRH transport. The ac conductance in 1 wt. % sample is expressed by sigma(omega) proportional to omega(s), and the temperature dependence of s follows the correlated barrier hopping model. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4749264]

Counter-ion dependent, longitudinal unzipping of multi-walled carbon nanotubes to highly conductive and transparent graphene nanoribbons - Shinde, Dhanraj B.; Majumder, Mainak; Pillai, Vijayamohanan K. (Scientific Reports, 2014)
Here we report for the first time, a simple hydrothermal approach for the bulk production of highly conductive and transparent graphene nanoribbons (GNRs) using several counter ions from K2SO4, KNO3, KOH and H2SO4 in aqueous media, where, selective intercalation followed by exfoliation gives highly conducting GNRs with over 80% yield. In these experiments, sulfate and nitrate ions act as a co-intercalant along with potassium ions resulting into exfoliation of multi-walled carbon nanotubes (MWCNTs) in an effective manner. The striking similarity of experimental results in KOH and H2SO4 that demonstrates partially damaged MWCNTs, implies that no individual K+, SO42- ion plays a key role in unwrapping of MWCNTs, rather this process is largely effective in the presence of both cations and anions working in a cooperative manner. The GNRs can be used for preparing conductive 16 k Omega sq(-1), transparent (82%) and flexible thin films using low cost fabrication method.

C@SiNW/TiO2 core-shell nanoarrays with sandwiched carbon passivation layer as high efficiency photoelectrode for water splitting - Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Shelke, Manjusha V. (Scientific Reports, 2014)
One-dimensional heterostructure nanoarrays are efficiently promising as high performance electrodes for photo electrochemical (PEC) water splitting applications, wherein it is highly desirable for the electrode to have a broad light absorption, efficient charge separation and redox properties as well as defect free surface with high area suitable for fast interfacial charge transfer. We present highly active and unique photoelectrode for solar H-2 production, consisting of silicon nanowires (SiNWs)/TiO2 core-shell structures. SiNWs are passivated to reduce defect sites and protected against oxidation in air or water by forming very thin carbon layer sandwiched between SiNW and TiO2 surfaces. This carbon layer decreases recombination rates and also enhances the interfacial charge transfer between the silicon and TiO2. A systematic investigation of the role of SiNW length and TiO2 thickness on photocurrent reveals enhanced photocurrent density up to 5.97 mA/cm(2) at 1.0 V vs. NHE by using C@SiNW/TiO2 nanoarrays with photo electrochemical efficiency of 1.17%.

Co3O4 nanorods-efficient non-noble metal electrocatalyst for oxygen evolution at neutral pH - Ramsundar, Rani M.; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Joy, Pattayil Alias (Electrocatalysis, 2015)